DISCIPLINARY CULTURE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN IMPROVING STUDENTS' WORSHIP EXPERIENCE - Aimang, Hasrat A (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Discipline is a very important attitude because its application can develop a person who can control himself effectively. When someone is bound by rules then tries to follow them, it keeps them from doing what they want and out of control. A good teacher is a teacher who has a disciplined attitude on duty. The research objective is to find out how discipline is enforced by Islamic religious education teachers in improving students' worship practices at SMP Negeri 1 Luwuk. The method in this study is a qualitative approach, in the form of data collection and interviews. The results showed that the Discipline of Islamic Religious Education Teachers in improving the Practice of Student Worship at SMP Negeri 1 Luwuk was carried out well by holding religious activities such as cults twice a month on Fridays. However, the discipline of Dzuhur Prayer in congregation at school has never been implemented due to limited space or the absence of a prayer room at the school. Based on the results of research on the Discipline of Islamic Religious Education Teachers in Improving Students' Worship Practice at SMP Negeri 1 Luwuk, it can be concluded that Islamic Religious Education Teachers focus on building morals and developing students' character, for religious activities such as cults being held twice a month, namely on Fridays 'at. However, the Dzuhur Prayer discipline in congregation at school has never been implemented due to limited space or the absence of a prayer room at SMP Negeri 1 Luwuk. Discipline of Islamic Religious Education Teachers can improve Student Worship Practice